SISTEM KEAMANAN BRANKAS MENGGUNAKAN KUNCI OTOMATIS DENGAN SMS - Nurul Chafid; Zulkifli (JURNAL SATYA INFORMATIKA, 2021)
Along with the developments in the world of information technology and computer network technology is increasing rapidly with the increase in technology, the evil in the world or in the virtual world is rapidly increasing with the advent of the hackers, and other snippets, thus pursued a variety of ways to secure the data and perhaps valuable goods, and the crime rate is quite high, especially in the theft of money to encourage the establishment of a safe deposit box safety device that is capable of providing effective security. This device consists of several important parts namely part series Microcontroller AT89S51, Wavecom GSM module, Solenoid and hand phones as a medium to transmit data. This tool is designed as a safety system that is applied to the key safe that works automatically. This security system using microcontroller AT89S51 as the central data processing of all existing systems. The working principle of this system is always active when the tool is connected to the voltage source. The system utilizes hand phones media that serves to send an SMS containing the password to access the safe, then the SMS will be received by the GSM module and processed by a microcontroller.